Medium‐chain fatty acid esters are effective even in azole‐resistant Malassezia pachydermatis. Issue 12 (16th August 2022) - Koch, Christin; Nordzieke, Steffen; Grieger, Jessica; Mayser, Peter
Abstract: Background: Malassezia (M.) pachydermatis as a frequent reason for dermatological consultation in dogs and cats was recently shown to be lipid‐dependent, too. Lipolytic activity is a prerequisite for activating antimicrobial effectivity of fatty acid esters. Objectives: It was therefore of interest whether it is possible to induce this mechanism in M. pachydermatis and to identify possible differences between minimal and strong lipid‐dependent strains. Methods: In an agar dilution test, the minimal inhibitory concentrations of six fatty acid esters were determined for seventeen M. pachydermatis strains. GC analysis of parent compounds and liberated fatty acids was used to quantify ester cleavage. Results: Hydrolysis was observed in all test strains in a homogenous manner but was dependent on the chemical structure. Lowest MICs (500 ppm after 14 days of incubation) were obtained applying glyceryl monocaprylate and 3‐hydroxylpropyl caprylate, while the corresponding esters of undecylenic acid showed nearly twice the value. As shown by GC analysis with the reference strains CBS 1879 and CBS 1892 and 3‐hydroxypropyl caprylate, hydrolysis and caprylic acid formation starts immediately and was dependent on yeast density. Furthermore, nine azole‐resistant strains isolated from dogs with treatment failures showed MIC values comparable to the other strains and no resistance to monohydric fatty acid esters. Conclusions: Medium‐chain fatty acid esters may represent a new therapeutic option for veterinary use even in azole‐resistant strains. The in vivo verification in M. pachydermatis ‐associated dermatitis in dogs and cats will be the next step for the successful development of new therapeutics.